The Phenomenon of Child Abuse in Islamic Boarding Schools: A Power Relations Perspective and Islamic Education Reform - Stiawati, Titi; Sulisman, Alya Nurayu (Universitas Sultan Ageng Tirtayasa, 2025)
The phenomenon of violence against children in Islamic boarding schools has become an urgent issue to be addressed systematically. This article aims to explore cases of child abuse in pesantren through a descriptive qualitative approach with Michel Foucault's theoretical framework on power relations. In the context of pesantren, power relations between teachers and santri are often hierarchical and unbalanced, creating a situation that allows for the abuse of power. Violence, both physical and sexual, reflects not only individual violations but also systemic problems influenced by a culture of absolute obedience and lack of supervision. Based on data analysis and in-depth interviews, this article identifies the root causes and offers strategic recommendations, including reform of pesantren culture, strengthening of regulations, and provision of safe complaint mechanisms. The article emphasizes the need for collaborative measures between the government, pesantren, and communities to create a child-friendly educational environment and support their rights.